gtajphillips gtajphillips
  • 03-03-2019
  • Mathematics
contestada

FIND the inverse of f(x)= -6 -x^1/3

f^-1 (x) =

Respuesta :

remotecontrolbrain
remotecontrolbrain remotecontrolbrain
  • 03-03-2019

Answer:

[tex]f^{-1}(x) = - (x+6)^3[/tex]

Step-by-step explanation:

Use the x-swap-y method to find the inverse:

[tex]y = -6 -x^{1/3}\\x\leftrightarrow y\\x = -6-y^{1/3}\,\,\,\mbox{and solve for y:}\\-x-6=y^{1/3}\\(-(x+6))^{3}=y\\y = - (x+6)^3[/tex]

Answer Link

Otras preguntas

please help i am confused
How to send large video files without losing quality
How many times did emancipation fail in congress during the civil war
If we randomly select 2 students at a time and record their drinking habits, what is the probability that both students drink
Given P(E or F) = 0.69, P(E) = 0.49, and P(E and F) = 0.06, what is P(F)?
If a cell becomes freely permeable to sodium ions (na ) and is not regulated, what will be the resulting membrane potential?
Find the critical t-value that corresponds to % confidence. Assume degrees of freedom
The concept of sustainable development draws particular attention to the well-being of
What did the events of 1968 show about americans views on plitics at the time
A={2,4,6,…,18,20} then n(A)=